Animal sourced foods and child stunting - Headey, Derek D.; Hirvonen, Kalle; Hoddinott, John F. (International Food Policy Research Institute, 2017)
Stunting affects 160 million pre-school children around the world, and imposes significant costs on a child’s health, cognitive development, schooling and economic performance. Stunting in early childhood has been linked to poor dietary diversity, notably low intake of animal-sourced foods (ASFs) rich in high quality protein and other growth-stimulating nutrients. Surprisingly, however, very little economic research has focused on ASFs and child growth. In this paper we redress this omission through an analysis of 112,553 children aged 6-23 months from 46 countries. We first document distinctive patterns of ASF consumption among children in different regions, particularly highly variable patterns of dairy consumption, low consumption of eggs and meat, and surprisingly frequent consumption of fish in several poor regions of Africa and Asia. We then examine how ASF consumption is associated with child stunting in multivariate models saturated with control variables.